Inovasi dan Transformasi Digital Modern Dalam Pengembangan Pembangunan Sosial Dan Komunitas Internasional - Fathiah; Zahriah; Lasri; Nurliana; Rizki Julia Utama (Bansigom Na Publisher, 2024)
Innovation and digital transformation today play an important role in affecting various aspects of people's lives, including in the social, cultural, economic, and political spheres. Advances in information and communication technology have changed the way people interact, communicate, learn, and work. Various virtual communities are emerging, enabling individuals to connect through digital media to share information, exchange ideas, and build relationships unlimited by distance and time. (Widyaningrum, 2021). Digital transformation has also affected the productivity and performance of organizations, including UMKM, where the use of digital technology can help boost productiveness and profitability. However, the process of digital transformation also requires changes in organizational behavior and culture. By leveraging digital technology, organizations can be more flexible, efficient, and innovative, which can ultimately improve competitiveness and long-term profitability